Impact of internal audit efficiency on effectiveness of financial management in public sector organizations: A case study of local government authorities in Shinyanga Region - Kitojo, Christian (Mzumbe University, 2024)
A research report submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Accounting and Finance of Mzumbe University